Anthropogenic Noise and Its Footprint on ELF Schumann Resonance Recordings - Tritakis, V.; Contopoulos, I.; Florios, C.; Tatsis, G.; Christofilakis, V.; Baldoumas, G.; Repapis, C. (Frontiers in Earth Science, 2021)
A set of various short artificial noises were generated deliberately in order to identify their footprint on the recordings of atmospheric electromagnetic ELF radiation in the Schumann Resonances band (from about 2 to 50 Hz). We expect that our work will assist fellow scientists to differentiate between artificial signals created from anthropogenic activity and real signals attributable to geophysical phenomena.